Multiple colony antifungal susceptibility testing detects polyresistance in clinical Candida cultures: a European Confederation of Medical Mycology excellence centers study. (September 2022) - Knoll, Miriam A.; Lackner, Nina; Ulmer, Hanno; Samardzic, Eldina; Steinmann, Joerg; Krause, Robert; Verhasselt, Hedda L.; Rath, Peter-Michael; Fuchs, Frieder; Koehler, Philipp; Denis, Blandine; Hamane, Samia; et al.
Abstract: Objectives: Many factors influence the outcome of in vitro antifungal susceptibility testing (AFST), including endpoint definition, inoculum sizes, time and temperature of incubation, and growth medium used. This European Confederation of Medical Mycology (ECMM) Excellence center driven study investigated multiple colony testing (MCT) of five separate colonies to investigate the prevalence of polyresistance (PR), defined as heterogeneous MICs from a same-species Candida culture irrespective of the underlying resistance mechanism. Methods: Candida spp . MCT for fluconazole and anidulafungin was performed by Etest prospectively comprising 405 clinical samples. MCT results were compared to the real-life routine MIC data and PR was assessed. Candida colonies displaying strong PR were selected for genotyping using multilocus sequence typing and random amplified polymorphic DNA assays for C. lusitaniae . Results: Candida PR was observed in 33 of 405 samples (8.1%), with higher rates for non- albicans species (26/186, 14%) than for C. albicans (7/219, 3.2%), and for fluconazole than for anidulafungin. MCT detected acquired resistance more often than routine AFST (18/405, 4.5%) and 9 of the 161 investigated blood cultures showed PR (5.6%). Multilocus sequence typing and random amplified polymorphic DNA did not reveal a uniform genetic correlate in strains studied. Conclusions: This study shows that Candida single MIC-values obtained in routine diagnostics may be incidental, as they fail to detect PR and resistant subpopulations reliably. The reasons for PR seem to be manifold and should be regarded as a phenotypical expression of genomic variability irrespective of the underlying resistance mechanism, which may help to interpret ambiguous and non-reproducible AFST results.